Emerging Anthelmintic Resistance in Poultry: Can Ethnopharmacological Approaches Offer a Solution? - Gerald Zirintunda; Savino Biryomumaisho; Keneth Iceland Kasozi; Keneth Iceland Kasozi; Gaber El-Saber Batiha; John Kateregga; Patrick Vudriko; Sarah Nalule; Deogracious Olila; Mariam Kajoba; Kevin Matama; Mercy Rukundo Kwizera; et al. (Frontiers Media S.A., 2022)
Limited pharmacological studies have been conducted on plant species used against poultry helminths. The objective of this study was to provide a basis for plant based anthelmintics as possible alternatives against poultry anthelmintic resistance. The study justified the need for alternative anthelmintics. The study places emphasis on the increasing anthelmintic resistance, mechanism of resistance, and preparational protocols for plant anthelmintics and their associated mechanism of action. Pharmaceutical studies on plants as alternative therapies for the control of helminth parasites have not been fully explored especially in several developing countries. Plants from a broad range of species produce a wide variety of compounds that are potential anthelmintics candidates. Important phenolic acids have been found in Brassica rapa L. and Terminalia avicenniodes Guill. and Perri that affect the cell signaling pathways and gene expression. Benzo (c) phenanthridine and isoquinoline alkaloids are neurotoxic to helminths. Steroidal saponins (polyphyllin D and dioscin) interact with helminthic mitochondrial activity, alter cell membrane permeability, vacuolation and membrane damage. Benzyl isothiocyanate glucosinolates interfere with DNA replication and protein expression, while isoflavones from Acacia oxyphylla cause helminth flaccid paralysis, inhibit energy generation, and affect calcium utilization. Condensed tannins have been shown to cause the death of nematodes and paralysis leading to expulsion from the gastro-intestinal tract. Flavonoids from Chenopodium album L and Mangifera indica L act through the action of phosphodiesterase and Ca2+-ATPase, and flavonoids and tannins have been shown to act synergistically and are complementary to praziquantel. Artemisinins from Artemisia cina O. Berg are known to disrupt mitochondrial ATP production. Terpenoids from Cucurbita moschata L disrupt neurotransmission leading to paralysis as well as disruption of egg hatching. Yeast particle encapsulated terpenes are effective for the control of albendazole-resistant helminths.